2003
DOI: 10.1258/002367703762226665
|View full text |Cite
|
Sign up to set email alerts
|

The Himalayan rabbit (Oryctolagus cuniculus L.): spontaneous incidences of endpoints from prenatal developmental toxicity studies

Abstract: SummaryT he historical database represents the spontaneous, i.e. normal changes of charact ers, in laboratory animals, and is a must for the assessment of toxic effects of compounds. For the Himalayan rabbit (CHBB:HM , SPF) bac kground data were collected from the control groups of regulatory studies between 1968±1999 in the Biberach laboratory of Boehringer Ingelheim (Germany). In the present study these data were compared with the bac kground data from the years 1974±1984, with those from the Ingelheim labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
6
1
1
Order By: Relevance
“…The average numbers of implantations and live fetuses were slightly higher than those of NZW rabbits reported by Kimmel and Price (1990) and Feussner et al. (1992) and of Himalayan rabbits reported by Viertel and Trieb (2003).…”
Section: Resultscontrasting
confidence: 56%
See 3 more Smart Citations
“…The average numbers of implantations and live fetuses were slightly higher than those of NZW rabbits reported by Kimmel and Price (1990) and Feussner et al. (1992) and of Himalayan rabbits reported by Viertel and Trieb (2003).…”
Section: Resultscontrasting
confidence: 56%
“…The values of reproductive parameters were not clearly different from those in previous surveys in Japan (Kameyama et al 1980;Morita et al 1987;Nakatsuka et al 1997). The average numbers of implantations and live fetuses were slightly higher than those of NZW rabbits reported by Kimmel and Price (1990) and Feussner et al (1992) and of Himalayan rabbits reported by Viertel and Trieb (2003). Tables S1 and S2 Tables S3 and S4, respectively.…”
Section: Mating and Cesarean Section Datamentioning
confidence: 52%
See 2 more Smart Citations
“…In den meisten Fällen werden die Wanderratte (R attus norvegicus Berkenhout) als Nager und das Kaninchen ( Oryctolagus cuniculus Linné) als Nichtnager eingesetzt. Kaninchen sind deutlich empfindlicher als Ratten gegenüber Teratogenen wie Thalidomid und daher für die Prüfung der toxischen Wirkung einer Prüfsubstanz auf die Embryonalentwicklung sehr gut geeignet. Warum zusätzlich die weniger empfindliche Ratte?…”
Section: Versuche An Ratten Und Kaninchenunclassified